Workstyle : be well, work better, do good - Penny, Lizzie; Hirst, Alex (Ascent Audio, 2023)
The industrial age routine of a 9-5 fits-all working system might finally be being dismantled, but what will replace it, and will it work for you? This thoughtful and practical book sketches out new approaches to individualized working styles which prioritize wellbeing, productivity, and fairness. If you are an ambitious Gen Z or millennial at the start of a career, looking for a job which works with your ethical framework, an experienced professional moving into a leadership role, or a business owner, CEO, manager, or HR professional, this book provides a vital contemporary overview of what will work best in a business world which is newly flexible, imaginative, neurodiverse, and accountable. It will help you create a way of working which frees your best people, liberates your potential, and allows you to stand out and do your best work-how it suits you best. Written by the inventors of the term workstyle, this book will relieve you of your ancestors' conditioning, inspire you to create a workstyle for yourself, and enable you to take part in the most significant change to working practices since 1817. By giving you the complete freedom to identify and pursue a way of working which fits around the unique nature of your lifestyle, you can be well, work better, and do good.